2013
DOI: 10.3389/fchem.2013.00021
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanoid-free perovskite oxide catalyst for dehydrogenation of ethylbenzene working with redox mechanism

Abstract: For the development of highly active and robust catalysts for dehydrogenation of ethylbenzene (EBDH) to produce styrene; an important monomer for polystyrene production, perovskite-type oxides were applied to the reaction. Controlling the mobility of lattice oxygen by changing the structure of Ba1 − xSrxFeyMn1 − yO3 − δ (0 ≤ x ≤ 1, 0.2 ≤ y ≤ 0.8), perovskite catalyst showed higher activity and stability on EBDH. The optimized Ba/Sr and Fe/Mn molar ratios were 0.4/0.6 and 0.6/0.4, respectively. Comparison of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Nonetheless, the sustainable activity observed for 45 h demonstrates the importance of thermodynamically stable rutile phase as support with Mn 3 O 4 as the active catalyst. Compared to the systems reported in the literature, [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Mn 3 O 4 supported over rutile TiO 2 is attractive, especially in terms of stability, and yield.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the sustainable activity observed for 45 h demonstrates the importance of thermodynamically stable rutile phase as support with Mn 3 O 4 as the active catalyst. Compared to the systems reported in the literature, [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Mn 3 O 4 supported over rutile TiO 2 is attractive, especially in terms of stability, and yield.…”
Section: Discussionmentioning
confidence: 99%
“…9 Sekine et al used pervoskite and reactions were conducted at 510 or 540 C at atmospheric pressure in the presence of steam; molar ratio of steam to EB was 2 or 12 with 22% ST yield for 30 min. 10 Venugopal et al has shown ceria containing hydrotalcite at 450 C at atmospheric pressure a marginally decreasing styrene yield from 47 to 45% over a period of 72 h. 11 Shin et al fed a balancing gas of water and EB in helium, over V 2 O 5 /CeO 2 -MgO and achieved EB conversion of 43% and ST selectivity of 91% at 600 C; prior to the activity measurement, the catalyst was activated in the steam ow of 50 mL min À1 by heating up to 650 C at the rate of 2.5 C min À1 . 12 Sivaranjani et al employed V-doped titania with molecular oxygen at 500 C and obtained about 50% ST yield initially; however it continuously decreases at higher time on stream.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative area of oxygen from H 2 O decrease slightly from 24.9 to 23.8%, indicating that the adsorbed molecular water mostly keep adsorption/desorption equilibrium during the ODH reaction, simultaneously, a little be decomposed at sites of oxygen vacancy to form active oxygen (O*) and active hydrogen (H*). 72,73 It is found that the oxygen from surface hydroxyls decreases distinctly from 15.3 to 11.2%, suggesting that the hydroxyl groups mould supply the activated oxygen or partial OH groups combine with H* to form water. The carbonyl group and carboxyl group may exhibit few contributions to ODH with tender change before and aer reaction according to our previous work.…”
Section: Promoting Effect Of Mnmentioning
confidence: 99%
“…51,74 In the presence of lattice oxygen, along with the cyclic redox between the both redox couples of Ce 4+ /Ce 3+ and Mn 4+ /Mn 3+ , and the migration of Mn to the surface of catalyst, the oxygen vacancies, activated oxygen, and activated hydrogen can be generated. According to literatures, 9,72,73,[75][76][77] the following chain of reactions can be occurred:…”
Section: Possible Promoting Mechanismmentioning
confidence: 99%